Rare bird documentation form for Northern Goshawk at Hickory Hill Park, 1982 - Staudt, Thomas J.et al (1982)
Rare bird documentation form for a Northern Goshawk at Hickory Hill Park in Johnson County, IA on November 16, 1982. Epson - sheet feed